Bifurcated Aneurysm Location Predicts In-Stent Stenosis After Neuroform-EZ Stent-Assisted Coiling for Intracranial Aneurysm - You, Wei; Feng, Junqiang; Ge, Huijian; Jin, Hengwei; Liu, Peng; Li, Youxiang; Jiang, Yuhua; Liu, Xinke (Frontiers in Neurology, 2022)
ABSTRACT BACKGROUND and PURPOSE The Neuroform EZ stent system (Boston Scientific Corporation, Fremont, CA, USA) is a fourth-generation intracranial aneurysm stent designed specifically for the cerebrovasculature to support aneurysm treatment. In the present study, we analyzed our consecutive series of aneurysm patients treated with Neuroform EZ stent, with special attention to the occurrence of ISS. METHODS A retrospective review of our center's electronic database was conducted to identify all patients with intracranial aneurysms who underwent aneurysm treatment with Neuroform EZ stent between January 2016 and October 2018. Patients with at least once digital subtraction angiography (DSA) follow-up in our hospital were enrolled in this study. In-stent stenosis (ISS) was graded as mild (<25%), moderate (25–50%), or severe (>50%). RESULTS The study included 114 patients (78 females, 68.4%; median age 57.2±9 years) with 116 aneurysms. Of the 116 lesions, 20 were identified with ISS (17.2%) at a mean follow-up of 6.9±1.7 months, and ISS was mild in 30% (6/20), moderate in 50% (10/20), and severe in 20% (4/20). No patients were symptomatic or required further intervention. Patients developing ISS were younger than those without ISS (52.6±7.8 vs 57.9±9; p=0.016). The proportion of aneurysms located at the artery bifurcation was significantly higher in patients with stenosis than others (37.9% vs 10.3%; p=0.002). In multivariable analysis, the patient’s age (OR=0.94; 95% CI, 0.88-0.998; p=0.02) and bifurcated aneurysm location (OR=4.59; 95% CI, 1.54-13.67; p=0.006) were independent predictors of ISS. CONCLUSIONS In this retrospective study, the incidence of ISS after Neuroform EZ stent placement was 17.2%, and all ISS cases were asymptomatic. Patients with younger age and bifurcated aneurysm location are more likely to develop ISS. Although Neuroform EZ stent is particularly suitable for bifurcated aneurysms, the ISS for this location should be focused upon.